2016
DOI: 10.1016/j.jcin.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Successful Recanalization of Native Coronary Chronic Total Occlusion Is Not Associated With Improved Long-Term Survival

Abstract: Successful CTO-PCI compared with failed PCI was not associated with a lesser risk for mortality. However, successful CTO-PCI was associated with significantly less subsequent coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 30 publications
4
41
1
Order By: Relevance
“…Several previous observational studies and meta‐analysis regarding clinical outcomes in patients with successful CTO PCI have demonstrated its beneficial effect, such as improved survival rates and LV function, compared with failed PCI 1, 4, 5, 6, 8, 15. In contrast, some observational studies suggest that successful CTO PCI is not associated with improvement of survival rates and cardiovascular events 16, 17. Thus, these heterogeneous data obscure the necessity of PCI for CTO lesion, and thus it is important to assess whether a patient can gain beneficial effects from a CTO intervention before performing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous observational studies and meta‐analysis regarding clinical outcomes in patients with successful CTO PCI have demonstrated its beneficial effect, such as improved survival rates and LV function, compared with failed PCI 1, 4, 5, 6, 8, 15. In contrast, some observational studies suggest that successful CTO PCI is not associated with improvement of survival rates and cardiovascular events 16, 17. Thus, these heterogeneous data obscure the necessity of PCI for CTO lesion, and thus it is important to assess whether a patient can gain beneficial effects from a CTO intervention before performing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lee et al found no association of successful CTO-PCI on survival in 1173 elective patients with CTO 16. Nonetheless, previous studies were not randomised and lacked a comparison with a conservative control (CTO-No PCI).…”
Section: Discussionmentioning
confidence: 99%
“…Although several multicenter registries have evaluated PCI procedures in Korea,9)10)11)12)13) no nationwide contemporary PCI registries have been collected with standardized collection forms and unified reporting methods. The Korean Society of Cardiology (KSC) and Korean Society of Interventional Cardiology (KSIC) established the Korean percutaneous coronary intervention (K-PCI) registry to collect and report results in a standardized database for PCI case analysis throughout the country.…”
Section: Introductionmentioning
confidence: 99%